Analisis Pengaruh CAR dan BOPO Terhadap ROA Dengan NIM Sebagai Variabel Intervening Pada PT. Bank Pembangunan Daerah Kalimantan Periode Tahun 2011 – 2021 - Maulana Muhammad Ferly; Risal Rinofah; Ratih Kusumawardhani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the influence of CAR, and BOPO on Profitability or ROA with NIM as an intervening variable in the Bank Pembangunan Daerah Kalimantan period. 2011 – 2021. The population of this research is all Bank Pembangunan Daerah Kalimantan, namely 4 companies. The sampling technique used is the Purposive Sampling method, which is a sample taken with certain considerations. The consideration in question is the Bank Pembangunan Daerah Kalimantan which has complete financial data for 11 years, namely 2011 – 20 21. The data analysis method in this study is multiple regression analysis and path analysis using SPSS 26 software. Based on the results of the hypothesis test, it can be concluded that CAR partially has a positive and significant effect on NIM and Profitability (ROA). BOPO partially has a negative and significant effect on Net Interest Margin (NIM) and has a positive and significant effect on Profitability (ROA). NIM partially has a positive and significant effect on Profitability (ROA). Meanwhile, the Net Interest Margin (NIM) can mediate the influence of CAR and BOPO on the Profitability (ROA) of Bank Pembangunan Daerah Kalimantan for the 2011-2021 period.